FAKTOR PENGARUH PEMIKIRAN POLITIK GUS DUR TERHADAP IDE PEMBUKAAN HUBUNGAN DIPLOMATIK INDONESIA-ISRAEL - Widyasmoro Priatmojo (HI 16 UMY 135, 2016)
*135 Abdurrahman Wahid was a politician which had differences compared to others. Based on his level, people did not understand well about him. However he was a good person taking assertively any consequences. That was made him popular with the general public. At the time he had started to declare establishment of diplomatic relation Indonesia-Israel, people were against with curse. Abdurrahman Wahid were considered as drunken god because of irrational decision. However it gave strong impact to Indonesia’s stand toward Israel-Palestine conflict. This article tried to identify why his political thought appeared and aimed. The political thought should be determined by influences. That was what article explained. To address this problem, the analysis frame was political thought concept and political attitude theory which described factors of influences. The study will be organized on Background, internal factors, external factors, and Gus Dur’s political thought.